Competitiveness of Palm Oil Products in International Trade: An Analysis between Indonesia and Malaysia - Muhammad Arsyad; Achmad Amiruddin; Suharno Suharno; Siti Jahroh (Caraka Tani: Journal of Sustainable Agriculture, 2020)
The supply of palm oil products is still a central issue in international trade. Indonesia and Malaysia are major suppliers, contributing around 85% of world palm oil. Hence, both countries have an important role, as well as competing with each other in international trade. The palm oil products usually in high demand worldwide include Crude Palm Oil (CPO), which is the main and its derivative products such as Refined Bleached Deodorized (RBD) palm olein and Palm Fatty Acid Distillate (PFAD). Therefore, the research aims at assessing the competitiveness of palm oil products between Indonesia and Malaysia in international trade. The Revealed Comparative Advantage (RCA) and products mapping methods were used in this assessment. The results show that, the value of RCA of Indonesian CPO showed a negative trend, although, still higher than Malaysia, though with positive trend. However, Indonesian RBD palm olein and PFAD have a positive trend compared with Malaysia. Upon using the method of products mapping, it was found that, the palm oil products of both countries were in group A. This is an indication that the products have comparative advantage and export specialization. Therefore, there is need for strategic policies, in both countries, for supporting oil palm activities at the downstream. This will enhance the production of derivative products with the capacity of also meeting demands in the international trade.